Towards Sustainable Performance: Promoting Eco-Design in Green Supply Chain Management Practices - Abdullah, Rohani; Mohamad, Marini Nurbanum; Thurasamy, Ramayah (International Journal of Supply Chain Management, 2019)
This paper explores the green supply chain management practices adoption among Malaysian ISO 14001 certified manufacturing companies. The green practices that are measured in this research are eco-design, green purchasing and reverse logistics. This study used survey to collect responses from 616 manufacturing companies, with a response rate of 24.68%. The findings provided evidence that the level of green supply chain management practices has been implemented to a greater extent among responding firms. Specifically, the results have empirically proven that eco-design was the most highly adopted green practices among these manufacturing firms. In view of these findings, green supply chain management practices that involve external relationship with suppliers and customers (green purchasing and reverse logistics) have comparatively lower adoption than internally-focused green supply chain management practices (eco-design), which involves fewer external relationships. This paper provides the possible reasons for eco-design being the most adopted green practise among Malaysian ISO 14001 certified manufacturing companies and provides suggestions for firms in view of enhancing their sustainable performance through promoting eco-design in their green practices.